1000 Mini Cross Stitch Motifs - Welch, Sharon (Tunbridge Wells, Kent : SEARCH PRESS, 2013)
This fantastic resource and reference book for cross stitchers contains 1000 mini motifs for all occasions. Previously published as a paperback, this edition is in a larger format and with a flexible, lie-flat binding, making the charts even easier to read and use. The book includes all of the designs that made the previous edition so popular and is brimming over with ideas and inspiration for mini projects, gifts and samplers.
Includes index
Keywords: Cross-stitch -- Patterns; Cross-stitch